40Ar/39Ar ages of alkaline and tholeiitic rocks from the northern Deccan Traps: implications for magmatic processes and the K–Pg boundary - Parisio, L.; Jourdan, Fred; Marzoli, A.; Melluso, L.; Sethna, S.; Bellieni, G. (Geological Society Publishing House, 2016)
The Deccan large igneous province in India was emplaced temporally close to the Cretaceous–Palaeogene (K–Pg) boundary and is formed by tholeiitic flood basalts and less abundant alkaline rocks. Definition of the origin of Deccanmagmatism and of its environmental impact relies on precise and accurate geochronological analyses.We present new40Ar/39Ar ages from the northern sector of the province. In this area, tholeiitic and alkaline rocks were contemporaneously emplaced at 66.60 ± 0.35 to 65.25 ± 0.29 Ma in the Phenai Mata area, whereas rocks from Rajpipla and Mount Pavagadh yielded ages ranging from 66.40 ± 2.80 to 64.90 ± 0.80 Ma. The indistinguishable ages for alkaline and tholeiitic magmatism suggest that distinct mantle sources were synchronously active. The new ages are compared with previous ages, which were carefully screened and filtered and then recalculated to be comparable. The entire dataset of geochronological data does not support a time-related migration of the magmatismrelated to the northward Indian platemovement relative to the Reunion mantle plume. The main phase of magmatism, including the newly dated rocks from the northern Deccan, occurred at the K–Pg boundary. This suggests a causal link between the emplacement of the province and the K–Pg mass extinction.